Improving biofeedback for the treatment of fecal incontinence in women: implementation of a standardized multi‐site manometric biofeedback protocol. Issue 1 (24th July 2016) - Markland, A. D.; Jelovsek, J. E.; Whitehead, W. E.; Newman, D. K.; Andy, U. U.; Dyer, K.; Harm‐Ernandes, I.; Cichowski, S.; McCormick, J.; Rardin, C.; Sutkin, G.; Shaffer, A.; et al.
Abstract: Background: Standardized training and clinical protocols using biofeedback for the treatment of fecal incontinence (FI) are important for clinical care. Our primary aims were to develop, implement, and evaluate adherence to a standardized protocol for manometric biofeedback to treat FI. Methods: In a Pelvic Floor Disorders Network (PFDN) trial, participants were enrolled from eight PFDN clinical centers across the United States. A team of clinical and equipment experts developed biofeedback software on a novel tablet computer platform for conducting standardized anorectal manometry with separate manometric biofeedback protocols for improving anorectal muscle strength, sensation, and urge resistance. The training protocol also included education on bowel function, anal sphincter exercises, and bowel diary monitoring. Study interventionists completed online training prior to attending a centralized, standardized certification course. For the certification, expert trainers assessed the ability of the interventionists to perform the protocol components for a paid volunteer who acted as a standardized patient. Postcertification, the trainers audited interventionists during trial implementation to improve protocol adherence. Key Results: Twenty‐four interventionists attended the in‐person training and certification, including 46% advanced practice registered nurses (11/24), 50% (12/24) physical therapists, and 4% physician assistants (1/24). Trainers performed audio audits for 88% (21/24), representing 84 audited visits. All certified interventionists met or exceeded the prespecified 80% pass rate for the audit process, with an average passing rate of 93%. Conclusions & Inferences: A biofeedback protocol can be successfully imparted to experienced pelvic floor health care providers from various disciplines. Our process promoted high adherence to a standard protocol and is applicable to many clinical settings. Abstract : Our goal was to develop novel biofeedback protocols to improve standardization of clinical care for fecal incontinence in a multicenter clinical trial. Separate biofeedback protocols addressed the most common causes for fecal incontinence: strength exercises, sensory perception, and urge resistance. Centralized training along with the use of standardized patient models was an effective method for teaching the biofeedback protocols. Auditing of the biofeedback visits revealed high adherence to the biofeedback protocols. View the podcast on this paper at the following sites: iTunes:https://itunes.apple.com/gb/podcast/neurogastroenterology-motility/id1183308675 YouTube:https://youtu.be/OgRay1WjiNs